2001
DOI: 10.1002/jcb.1202
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α mediates RANK ligand stimulation of osteoclast differentiation by an autocrine mechanism†

Abstract: Osteoblasts or bone marrow stromal cells are required as supporting cells for the in vitro differentiation of osteoclasts from their progenitor cells. Soluble receptor activator of nuclear factor-kappaB ligand (RANKL) in the presence of macrophage colony-stimulating factor (M-CSF) is capable of replacing the supporting cells in promoting osteoclastogenesis. In the present study, using Balb/c-derived cultures, osteoclast formation in both systems-osteoblast/bone-marrow cell co-cultures and in RANKL-induced oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
114
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 61 publications
14
114
1
Order By: Relevance
“…LPS is well known to elicit TNF-α (Abu-Amer et al 1997;Zou and Bar-Shavit 2002;Itoh et al 2003), IL-6 (Itoh et al 2003;Sato et al 2004), IL-1α (Hong et al 2004), andIL-1β (Itoh et al 2003) release from monocytes. It is also well established that these cytokines promote Oc formation (Jimi et al 1999;Azuma et al 2000;Zhang et al 2001;Zou et al 2001;Kudo et al 2003;Wei et al 2005). We have confirmed their pro-osteoclastogenic properties but also shown for the first time that these cytokines are released by RANKL-primed pOcs autonomously when exposed to LPS (Fig.…”
Section: Figsupporting
confidence: 80%
See 1 more Smart Citation
“…LPS is well known to elicit TNF-α (Abu-Amer et al 1997;Zou and Bar-Shavit 2002;Itoh et al 2003), IL-6 (Itoh et al 2003;Sato et al 2004), IL-1α (Hong et al 2004), andIL-1β (Itoh et al 2003) release from monocytes. It is also well established that these cytokines promote Oc formation (Jimi et al 1999;Azuma et al 2000;Zhang et al 2001;Zou et al 2001;Kudo et al 2003;Wei et al 2005). We have confirmed their pro-osteoclastogenic properties but also shown for the first time that these cytokines are released by RANKL-primed pOcs autonomously when exposed to LPS (Fig.…”
Section: Figsupporting
confidence: 80%
“…It also contrasts an in vitro study using Balb/c and C57 mice that revealed TNFR1 but not TNFR2 dependence (Zou et al 2001). Interestingly, the latter study demonstrated that LPS induced release of TNF-α which then promoted Oc formation FIG.…”
Section: Figmentioning
confidence: 70%
“…For example, a minuscule amount of RANKL is sufficient to synergize with TNF-a to promote osteoclastogenesis from precursor cells. 17,41,47 Figure 5 DcR3-induced osteoclast formation is dependent on ERK and p38 MAPK activation. RAW264.7 cells (a) and human monocytes (b) were pretreated with vehicle, 50 mM PD98059, 1 mM U0126, or 1 mM SB203580 for 20 min prior to stimulation with DcR3 (3 mg/ml), M-CSF, or RANKL.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our previous study showed that EGCG reduces the interleukin-6 synthesis by platelet-derived growth factor without affecting the p70 S6 kinase activation (26). It is generally recognized that platelet-derived growth factor receptor has an intrinsic protein tyrosine kinase activity, whereas TNF-α receptor belongs to the cytokine receptor superfamily, and that the signal transduction mechanisms are quite different from each other (12,27). Thus, it appears likely that different and rather opposite effects of EGCG on p70 S6 kinase activation and interleukin-6 synthesis induced by TNF-α or PDGF-BB in osteoblast-like MC3T3-E1 cells are due to the difference between each receptor-mediated intracellular signaling.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to bone metabolism, TNF-α stimulates the activation of RANK in osteoclasts through RANK ligand expression in osteoblasts, which acts as a potent stimulator of osteoclastogenesis (12). It has been reported that TNF-α stimulates the synthesis of interleukin-6 (13).…”
Section: Introductionmentioning
confidence: 99%